Evaluation of MRSASelect™ Chromogenic Medium for the Early Detection of Methicillin-Resistant Staphylococcus aureus from Blood Cultures. Issue 4 (2013) - Manickam, Kanchana; Walkty, Andrew; Lagacé-Wiens, Philippe RS; Adam, Heather; Swan, Barbara; McAdam, Brenda; Pieroni, Peter; Alfa, Michelle; Karlowsky, James A
Abstract : INTRODUCTION: Staphylococcus aureus bacteremia is associated with considerable morbidity and mortality. In theory, reducing the turnaround time in reporting of methicillin-resistant S aureus (MRSA) among patients with bactermia could assist with the rapid optimization of antimicrobial therapy. OBJECTIVE: To evaluate the sensitivity and specificity of MRSA Select (Bio-Rad Laboratories, USA), a chromogenic medium, in the early detection of MRSA from blood cultures growing Gram-positive cocci in clusters, and to confirm that routine use of this medium would, in fact, reduce turnaround time for MRSA identification. METHODS: The present study was conducted at three microbiology laboratories in Manitoba. Between April 2010 and May 2011, positive blood cultures with Gram-positive cocci in clusters visualized on Gram stain were subcultured to both MRSA Select and routine media. MRSA isolates were identified using conventional microbiological methods from routine media and using growth with the typical colony morphology (pink colony) on MRSA Select medium. RESULTS: A total of 490 blood cultures demonstrating Gram-positive cocci in clusters on Gram stain were evaluated. S aureus was recovered from 274 blood cultures, with 51 S aureus isolates (51 of 274 [18.6%]) identified as MRSA. MRSA Select medium had a sensitivity of 98%, a specificity of 100%, a positive predictive value of 100% and a negative predictive value of 99.8% for the recovery and identification of MRSA directly from positive blood culture bottles. In addition, use of MRSA Select medium was found to improve turnaround time in the detection of MRSA by almost 24 h relative to conventional methods. DISCUSSION: These data support the utility of MRSA Select medium for the rapid identification of MRSA from positive blood cultures. Further clinical studies are warranted to determine whether the improvement in turnaround time will result in a measurable reduction in suboptimal antimicrobial therapy and/or improvement in patient outcome.